L’Imaginaire Linguistique à l’intérieur de la diversité dans la langue - Sanda-Maria ARDELEANU (Anadiss, 2012)
The language education policies in the context of globalisation emphasize the necessity of a plurilingual education promoting cultural diversity. The present study offers an insight into the current situation of the French language. The author underlines the essential role linguistic imaginary holds in the process of learning a foreign language. That is why she suggests cultivating a new attitude in the speakers of French based on the foundations of language diversity, as well as the diversity within one and the same language.